Kinerja Pegawai: Bagaimana Kontribusi Kompensasi dan Disiplin Kerja Sebagai Determinan dalam Meningkatkan Kinerja - Ludin, Ismail; Solihin, Anip; Pratami, Ayu (Value : Journal of Management and Business, 2026)
Performance is a crucial part of an organization since it is a measure for whether an organization has succeeded in attaining its goals in the short, medium, or long term. Employee performance at Serang City Regional General Hospital has declined. The purpose of this study is to ascertain how pay and work ethics affect employee performance. This study used a quantitative strategy by gathering data from 99 respondents. A questionnaire disseminated using the KoboToolbox platform was used to collect primary data. Then, using SPSS version 26 software, the gathered data was examined utilizing statistical tests and hypothesis testing with multiple linear regression techniques. The findings demonstrated that employee performance was not substantially impacted by pay. Nonetheless, employee performance was significantly impacted by both factors compensation and work discipline with work discipline having the greatest impact. The combined impact of the two independent factors was 31.2%.